E-M calculation model and its application of calculating deformation in a new tunnel orthogonally undercrossing an existing tunnel. (May 2022) - Liu, Xinrong; Wang, Linfeng; Zhou, Xiaohan; Wang, Jiming; Zhong, Zuliang; Liu, Peng; Xiong, Fei; He, Chunmei
Highlights: A calculation model for vertical deformation of an existing tunnel undercrossed by a new tunnel. The global sensitivity analysis of the parameters in the E-M calculation model. The influence mechanism of parameters on vertical deformation of the existing tunnel. The influence zone of an existing tunnel undercrossed by a new tunnel. Abstract: A new tunnel orthogonally undercrossing an existing tunnel at a close distance inevitably affects the deformation of the existing tunnel. Analytical calculation methods of the deformation of an existing tunnel orthogonally undercrossed by a new tunnel remain underdeveloped. Based on the principles of the equivalent layer method and mirror method, a new calculation model (E-M calculation model) for the vertical deformation of an existing tunnel undercrossed by a new tunnel in multi-layered strata is proposed, and the accuracy of the model in calculating the vertical deformation of the existing tunnel is verified by on-site monitoring data and numerical simulation. An L 25 (5 6 ) orthogonal test table is designed to conduct a sensitivity analysis on the parameters that affect the vertical deformation of the existing tunnel. The diameter of the new tunnel D 2, the burial depth of the existing tunnel H 1 and the distance between the new tunnel and the existing tunnel ΔH are the main factors affecting the deformation of the existing tunnel. Among them, ΔH mainly affects the shape of the settlement curve of the existing tunnel. The settlement of the existing tunnel Uz has a quadratic correlation with the diameter of the new tunnel D 2 and a linear correlation with the burial depth of the existing tunnel H 1 . The major influence zone of the existing tunnel undercrossed by the new tunnel is -i < x < i (i is between 6.33 m and 8.35 m, and × is the distance to the tunnel axis), while the minor influence zone is an uncertain range. For safety, the area of the major influence zone can be appropriately enlarged in practical engineering applications.